2020
DOI: 10.7307/ptt.v32i5.3499
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Weather Conditions on Travel Demand – The Most Common Research Methods and Applied Models

Abstract: This paper presents an overview of the applied research methodologies and developed travel demand models that take weather impact into account. The paper deals with trip generation and modal split as elements of travel demand that best describe changes in the travel behaviour in different weather conditions. The authors herein emphasize the importance of research in local conditions in all climate zones, especially in areas where climate and modal split characteristics are different from those in common resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…On Researchers explored the impacts of adverse weather conditions on both transport demand and supply. When speaking about transport demand, previous studies have shown that adverse weather conditions lead to a significant change in modal distribution [10][11][12]. Also, adverse weather conditions increase the probability of a traffic accident [13,14].…”
Section: Survey Methodologymentioning
confidence: 99%
“…On Researchers explored the impacts of adverse weather conditions on both transport demand and supply. When speaking about transport demand, previous studies have shown that adverse weather conditions lead to a significant change in modal distribution [10][11][12]. Also, adverse weather conditions increase the probability of a traffic accident [13,14].…”
Section: Survey Methodologymentioning
confidence: 99%
“…They found that cycling and walking in spring and autumn are more affected by temperature variations in northern Sweden than in central and southern Sweden [16]. Against this background, Dragana, Ivan, Vladimir and Jadranka [2], who conducted an extensive literature review of investigations of the impacts of weather conditions on travel demand, However, not all of the survey participants reported the exact addresses of their points of departure and arrival, meaning the data set does not include grid cells for all of the trips reported. The grid cells of the points of departure, however, were needed to identify the nearest weather stations.…”
Section: Introductionmentioning
confidence: 99%
“…Various scholars have demonstrated the importance of the effect of weather conditions on people's mobility behaviour in the past two decades [1,2]. In general, active modes such as walking and cycling appear to be more sensitive to weather conditions than travelling by car or public transport [3].…”
Section: Introductionmentioning
confidence: 99%